Design and Implementation of Microcontroller-Based Building Automation for Smart Computer Laboratory - Hatta, Puspanda; Dadungawigra, Dimmapraha Fatuardi; Budianto, Aris (Universitas Sebelas Maret, 2019)
This research provided device management automation for computer laboratories using Arduino. Some devices in computer laboratories such as Air Conditioners and LCD Projectors were always on while the device not used. It caused inefficient uses of electricity resulting in increased electricity bills and reduce the device lifetime. Device automation made the electronic devices work automatically. The first automation we applied on the Air Conditioner, the other one was on LCD Projectors. This schematic developed based on Arduino Uno R3 with several components such as the infrared transmitter, humidity sensor DHT11, relay board and I2C OLED display. Arduino Uno R3 provided as the central controller. The two methods of testing were used for measuring this system performance. The first test was done by testing the performance of the components used, such as the IR Transmitter, DHT11, relay board, and I2C OLED Display. The second test was done by testing the functionality of Arduino Uno R3 as a controller. This test resulted that the automation system can work properly with fully automatic control LCD projectors and air conditioners by periodically stabilizing room temperature and turning on the projector's LCD automatically when needed.